Pengaruh Kualitas Produk, Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan di Yoshinoya Grand Kota Bintang Bekasi - ANITA CHAERUNNISA; Salman Paludi (Eduturisma, 2023)
The purpose of this study is yo find the quality products, service quality and promotion of customer satisfication in the Yoshinoya Grand Kota Bintang Bekasi together in partial. This study used the classifications sample methodology, specifically in the non-probability at random of the sample with a pick who is calling or visiting Yoshinoya Grand Kota Bintang Bekasi to 100 people. Methods used to collect the data involves sharing a questionnaire with respondents, while prosess data collection conducted through the use of several software using SPSS linear regression 24 version. The result of this research competitive with the product quality, service quality and promotion of influential simultaneously on customer satisfaction in Yoshinoya Grand Kota Bintang Bekasi.